Beyond Perception: Integrating Institutional Support, Financial Literacy, and System Quality For M-Wallet Adoption Among MSMEs - Syah, Dedy Husrizal; Sumekar, Aried; Sagala, Gaffar Hafiz (Assets: Jurnal Akuntansi dan Pendidikan, 2026)
This study wants to bridge the gap between positive perceptions and actual adoption of fintech by integrating the perspectives of the Technology Acceptance Model (TAM), the Information Systems Success Model, Institutional Theory, and the Resource-Based View. This study aims to analyze the influence of financial literacy, government support, and vendor support on system quality and information quality, as well as the role of digital technology use on information quality on m-wallet platforms. Using a quantitative approach with Structural Equation Modeling (SEM-PLS), the study involved 214 MSME respondents in Medan City who use m-Wallet services. The results indicate that financial literacy and government support have a significant impact on system quality. Furthermore, both system quality and the use of digital technology positively affect information quality. However, vendor support does not affect system quality. Practically, this study found that system quality is a critical mediator of information quality, which is significant for business decision-making. Therefore, fintech developers should ensure the quality of fintech systems to provide credible information to business communities. This study also suggests that the government should enhance digital financial literacy programs and integrate them with fintech adoption policies.